The Red Army’s ‘Frontline Oppression’ at the Sandomierz Bridgehead (August 1944 – January 1945) - Robert Piwko (Review (Institute of National Remembrance))
This article is part of a current of research into social history during the Second World War, dealing with how the Red Army’s Sandomierz-Baranów bridgehead on the western bank of the Vistula operated from the second half of 1944 to the beginning of 1945. It draws upon testimonies confirming the occurrence of the phenomenon of the so-called ‘frontline oppression’ at the Sandomierz bridgehead. This term has been used to describe the negative aspects associated with the period when Soviet troops were stationed there. The forms of oppression included crimes and offences committed by individual soldiers or groups of Red Army soldiers against the inhabitants of the bridgehead or their property. In addition, other forms of oppression included organised actions, involving the over-exploitation of the products and raw materials from the area. Both individual and collective actions of this nature contributed to the deterioration of the quality of life and the condition of the community residing at the bridgehead at the time. The Sandomierz bridgehead was one of several parts of Polish territory where the German occupying authorities’ writ had ceased to run. The civilian administration was being exercised by offices subordinate to the Polish Committee of National Liberation (Polski Komitet Wyzwolenia Narodowego, PKWN), an authority dependent on and subordinate to the Soviet Union. Thus, the region of interest was part of a state which the Soviet authorities recognised as their ally. Despite that, the circumstances accompanying the stationing of the ‘allied’ Red Army at the bridgehead are much different from those that have been perpetuated over the years giving a one-sided and false picture of the presence of Soviet troops on Polish territory after 1944.